2013
DOI: 10.1371/journal.pone.0063644
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Altered Metabolic Pathways in Plasma and CSF in Mild Cognitive Impairment and Alzheimer’s Disease Using Metabolomics

Abstract: Alzheimer’s Disease (AD) currently affects more than 5 million Americans, with numbers expected to grow dramatically as the population ages. The pathophysiological changes in AD patients begin decades before the onset of dementia, highlighting the urgent need for the development of early diagnostic methods. Compelling data demonstrate that increased levels of amyloid-beta compromise multiple cellular pathways; thus, the investigation of changes in various cellular networks is essential to advance our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
283
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(323 citation statements)
references
References 66 publications
17
283
2
1
Order By: Relevance
“…Integrated information from CSF and plasma samples was used to select and validate reliable plasma biomarkers related to AD [123]. As expected, the number of affected pathways in both biofluids increased with disease progression.…”
Section: Metabolomics and Ad In Plasma And Serummentioning
confidence: 84%
See 2 more Smart Citations
“…Integrated information from CSF and plasma samples was used to select and validate reliable plasma biomarkers related to AD [123]. As expected, the number of affected pathways in both biofluids increased with disease progression.…”
Section: Metabolomics and Ad In Plasma And Serummentioning
confidence: 84%
“…As expected, the number of affected pathways in both biofluids increased with disease progression. Interestingly compared to control subjects near 30% and 60% of the metabolic pathways altered in the CSF of MCI and AD patients respectively, were also affected in plasma samples from the same individuals showing certain correlation between biofluids [123]. Amino acid and dipeptide content correlation between CSF and plasma was also accomplished by Fonteh et al including also urine in that case [98].…”
Section: Metabolomics and Ad In Plasma And Serummentioning
confidence: 90%
See 1 more Smart Citation
“…Multi-platforms based on the combination of complementary chromatographic science prior to MS detection have also been employed (Czech et al, 2012;Ibanez et al, 2013;Trushina et al, 2013a). Utilizing RP and HILIC, Trushina et al, (2013a) analysed 15 AD, 15 MCI and 15CN CSF samples, and found approximately 30% of the metabolic pathways altered in MCI compared to CN, and 60% in AD compared to CN.…”
Section: Csfmentioning
confidence: 99%
“…Utilizing RP and HILIC, Trushina et al, (2013a) analysed 15 AD, 15 MCI and 15CN CSF samples, and found approximately 30% of the metabolic pathways altered in MCI compared to CN, and 60% in AD compared to CN. This finding showed that the number of affected pathways increases with disease severity.…”
Section: Csfmentioning
confidence: 99%